AKTIVISME ARSIP DALAM KONSEP KEBERAGAMAN DENGAN MENGEDEPAN PERKEMBANGAN PENDIDIKAN DAN ILMU PENGETAHUAN DI INDONESIA - Saharul Hariyono; Hilma Nurullina Fitriani (Khazanah: Jurnal Pengembangan Kearsipan, 2022)
Archival activism is a concept about archivists' awareness of the social power of archives to create social justice. The writing of this article should describe the application of a concept of archival activism in diversity practices that actively document communities that are traditionally marginalized from historical narratives and complicated by the desire to remain autonomous so that they often lack trust due to exceptions in the past which then come to the fore in the development of education and science in Indonesia. The data were analyzed using archival activism and related to the acceptability of aspirational theory. The data analysis technique is in the form of inductive analysis which starts from the data found to produce conclusions that can be in the form of categorization or propositions. The results of the analysis show that there are closures and marginalizations of community archives analyzed, such as the presence of Prostitute who were initially considered an immoral transformed as one of the revolutions for Indonesian independence; bissu, which is considered a transvestite, turns out to be complex and dignified when compared to gender status in Thailand as described in the epic I La Galigo; Towani Tolotang community, whose condition with bissu was long ago identified as a community forced to choose a religion for population purposes, however in its resistance promoted formal politics not to incorporate elements of religion stipulated by law into their worship practices. Then these three communities showed preventive archives that could be used as a collective memory for education and science, thus placing this document as an archive that was initially inactive but turned into statically active. Thus the public will get information that provides more understanding for accountable interests so that the archive is static secondary.